2019
DOI: 10.1002/hed.26016
|View full text |Cite
|
Sign up to set email alerts
|

The risk of second primary tumors in head and neck cancer: A systematic review

Abstract: Background: Second primary tumors (SPTs) are a common cause of reduced life expectancy in patients treated for head and neck cancer (HNC). This phenomenon forms an area to be addressed during posttreatment follow-up.Methods: We conducted a systematic review of literature following PRISMA guidelines, from 1979 to 2019, to investigate incidence of SPTs, synchronous, and metachronous, in HNC population. Results: Our review includes data of 456 130 patients from 61 articles. With a minimum follow-up of 22 months, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 82 publications
(105 reference statements)
2
50
0
6
Order By: Relevance
“…According to literature, our study confirmed that SPT are common in patients with HNSCC and the may cause a reduced life expectancy in head and neck cancer patients (Coca‐Pelaz et al., 2020).…”
Section: Discussionsupporting
confidence: 84%
“…According to literature, our study confirmed that SPT are common in patients with HNSCC and the may cause a reduced life expectancy in head and neck cancer patients (Coca‐Pelaz et al., 2020).…”
Section: Discussionsupporting
confidence: 84%
“…The presence of a previous or synchronous cancer halves survival . Patients with cancer clearly are at a higher risk of developing a second primary cancer …”
Section: Tumor Factorsmentioning
confidence: 99%
“…Because HNSCC is related to lifestyle behavior that give rise to disease of multiple organs, this might explain the higher odds of patients having mild to severe liver disease as well as non-metastatic and metastatic malignancy that was observed in this study ( Table 2 ). Previous findings have shown tumors of lung and esophagus to be the most common secondary primary tumor in HNSCC patients apart from tumors in the head and neck region ( 30 ). In correlation with this, we found that patients had almost three times higher odds of having a cancer of the respiratory and intrathoracic organs at diagnosis.…”
Section: Discussionmentioning
confidence: 99%